An apparatus for treating building surfaces and the like - Aris, Ishak; Parvez Iqbal, A. K. M. (2006)

(untitled)
An apparatus to treat a surface of a building comprising of a vertically extendible frame structure adapted to received an end effector operational tool such as a spray gun, scapper and the like, mounted onto a support frame assembly, a means to move the extendible frame structure to and fro along a longitudinal x-axis of the support frame assembly, a mean to move the extendible frame structure to and fro along a longitudinal y-axis of the support frame assembly, and an electronic processor control to receve and perocess electronic signals of the position of the end effector operational tool and other components of the apparatus and to activate movements of the extendible frame structure to a desible spatial position.